2014
DOI: 10.1002/2013jd021173
|View full text |Cite
|
Sign up to set email alerts
|

Total ozone and Umkehr observations at Hoher Sonnblick 1994–2011: Climatology and extreme events

Abstract: Umkehr and total ozone measurements have been carried out at Hoher Sonnblick (47.05°N, 12.95°E; 3106 m above sea level) since 1994 with the Brewer MkIV #093 spectrophotometer. These measurements are used to investigate trends in total and vertically resolved ozone in the period 1994–2011 and for establishing an Umkehr climatology. A method to estimate daily thresholds for extreme events in total ozone (TO3) based on skewed log‐Weibull distributions is presented and applied to the record. An analysis of the suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 71 publications
3
17
0
Order By: Relevance
“…However no significant trend is observed in the magnitude of extreme events. These measurements were used to investigate vertically trends in total ozone in the period 1994-2011 and for establishing an climatology [18].…”
mentioning
confidence: 99%
“…However no significant trend is observed in the magnitude of extreme events. These measurements were used to investigate vertically trends in total ozone in the period 1994-2011 and for establishing an climatology [18].…”
mentioning
confidence: 99%
“…Previous studies used (1) fixed thresholds (e.g., Bojkov and Balis 2001;Brönnimann and Hood 2003), (2) time-varying thresholds based on the deviation from monthly means (e.g., Anton et al 2008;Koch et al 2005;Krzyscin 2002), or (3) the application of extreme value theory (e.g., Fitzka et al 2014;Rieder et al 2010aRieder et al , b, 2011Petropavlovskikh et al 2015) to determine low ozone episodes. Furthermore, only few studies focused on changes in the UV field during low ozone episodes and the general connection between low ozone episodes and UV extremes (e.g., Anton et al 2008;Fragkos et al 2016;Martinez-Lozano et al 2011;Rieder et al 2010c).…”
Section: A Joint Threshold Approach For the Analysis Of Ozone And Uv mentioning
confidence: 99%
“…Several studies investigated the evolution of low ozone episodes at mid-latitudes (Anton et al 2008;Bojkov and Balis 2001;Brönnimann and Hood 2003;Fitzka et al 2014;Frossard et al 2013;Hood et al 2001;Iwao and Hirooka 2006;James 1998;Koch et al 2005;Krzyscin 2002;Newman et al 1988;Petzoldt 1999;Rieder et al 2010aRieder et al , b, 2011Rieder et al , 2013. The definitions for low ozone episodes, often referred to as ozone miniholes, vary among studies, and to date, only few studies have analyzed changes in the UV field during low ozone episodes and the general connection between low ozone episodes and UV levels (e.g., Anton et al 2008;Bartlett and Webb 2000;Fragkos et al 2016;MartinezLozano et al 2011;McKenzie et al 1991;Rieder et al 2010c).…”
Section: Introductionmentioning
confidence: 99%
“…Analyses of interannual and long-term variability in total column ozone on regional (e.g., Mäder et al, 2007;Rieder et al, 2010aRieder et al, , b, 2011Fitzka et al, 2014) and global (e.g., Frossard et al, 2013;Rieder et al, 2013) scales have been presented in a number of recent studies. There is now a broad consensus that long-term negative ozone trends are domi-I.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, recent work analyzing the tails of the ozone distribution (i.e., the extremes) in relation to the bulk properties (i.e., the mean) has shown that analysis of the tails allows for a more systematic attribution of ozone changes to dynamical features than mean value analysis can achieve (e.g., Rieder et al, 2010aRieder et al, , b, 2011Rieder et al, , 2013Frossard et al, 2013). These studies also showed that even moderate NAO and ENSO events can have significant effects on the midlatitude ozone field.…”
Section: Introductionmentioning
confidence: 99%